Mode preference of intercity travel by stated preference method: A case study in Malaysia - Roza, A.; Adji, B.M.; Raja Abdul Aziz, R.S. (2011)
Bus is an important transport mode in intercity travel in Malaysia. Many reasons lie behind the preference of bus as an intercity transport, including income, transport budget, intercity travel frequency, age, occupation, gender, marital status, trip purpose, fare and travel time. This paper presents the outcome of a study on intercity bus passenger travel characteristics in Malaysia. A survey was conducted to study the intercity bus services between Kuala Lumpur and other cities in Malaysia. The survey was held on several selected intercity bus terminals. The stated preference method was employed in this study. Regression analysis was applied in the data analysis in order to obtain the logit model between bus preference with the variables that influence the transport mode preference. Sensitivity analysis had also been applied in this study to find the bus preference sensitivity toward the attribute value of changes.